The Value of Active Management in Equity Mutual Funds from the Perspective of Czech Individual Investor - Kölbl, Jan; Tyll, Ladislav; Kopkáně, Heřman; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
This thesis analyzed 97 actively managed equity mutual funds publicly distributed in the Czech Republic relatively to their benchmark and passively managed alternative. The results are generally consistent with the previous research from other developed countries. Net of fees, actively managed funds on average considerably underperform their benchmarks. From the 50 detailly analyzed active funds, 13 funds were identified as potential closet indexers. It was also confirmed that the annual management fee is a negative performance predictor. The above-mentioned results generally apply to all the analyzed regions (developed world, North America, Europe) but are less significant for the funds investing in the European market. The conducted analysis supports the current notion that a risk-averse individual investor should not invest in an actively managed fund when risk-adjusted profit maximization is his or her primary goal.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses